UPAYA MENINGKATKAN KETERAMPILAN MENYUSUN KATA PADA SISWA MENGGUNAKAN METODE SCRAMBLE DI SANGGAR BELAJAR KAMPUNG BHARU MALAYSIA - Miftahussudur, Miftahussudur; Syamsuyurnita, Syamsuyurnita (Universitas Muhammadiyah Makassar, 2025)
This study aims to improve students' word arranging skills at Kampung Bharu Learning Center, Malaysia, using the Scramble method. The research method used is Classroom Action Research (CAR) with a descriptive qualitative approach. The research subjects consisted of 20 students, divided into 12 females and 8 males. The study was conducted in two cycles, each consisting of planning, action implementation, observation, and reflection. Data collection techniques included observation, word arranging ability tests, student response questionnaires, and documentation. The results showed that the Scramble method was effective in enhancing students' word arranging skills, as indicated by the increase in average scores from 58% in the pre-cycle to 72% in the first cycle and 85% in the second cycle. Moreover, this method also increased student participation in learning from 40% in the pre-cycle to 70% in the first cycle and 90% in the second cycle. Student responses to the Scramble method were very positive, with 85% stating that the method helped them understand the material, 80% feeling more confident, and 90% finding the learning process more enjoyable. Based on these results, it can be concluded that the Scramble method is effective in improving students' word arranging skills and can be used as an innovative and enjoyable learning alternative.